Some reflections on EU law on adoptive parentage: Future perspectives - Sánchez Cano, María Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Legal-legal links arising from the institution of adoption can be problematic when they have an international element, whereby the situation would be linked to the legal systems of different States, the discrepancies of which could lead to claudicating decisions. In order to ensure the principles of the best interests of the child and non-discrimination, the European Parliament Resolution of 2 February 2017 on the cross-border aspects of adoption was adopted. Equally relevant is the Proposal for a Council Regulation on jurisdiction, applicable law, recognition of decisions and acceptance of authentic instruments in matters of parentage and the creation of a European Certificate of Parentage.